ANALISIS KUALITAS LAYANAN PENYIMPANAN CLOUD PADA NEXTCLOUD DAN PYDIO - Lalu Delsi Samsumar; Beni Ari Hidayatulloh; Zaenudin Zaenudin; Putri Novia Dyah Pitaloca (Journal of Information Technology and Its Utilization, 2023)
The development of information technology has greatly influenced the development of current storage media, such as cloud-based storage (cloud). Nextcloud and pydio storage are part of an open based cloud computing system. Measuring service quality can be seen from the aspects of throughput, delay, jitter, and packet loss. This research was conducted to compare the upload and download speeds between the nextcloud server and the pydio server. Of the two cloud storage servers, five trial upload and download respectively. Based on the test results showing that the upload and download processes produce final cloud storage data which has the highest average throughput in terms of uploading files of different types and capacities, the next cloud server is 1,934.6 kbps. The cloud storage that has the lowest average packet loss value is balanced, because the two cloud storages get the same packet loss value of 0%. The cloud storage that has the lowest average file upload delay is the nextcloud server at 222,585 ms. The cloud storage that gets the lowest jitter value is the pydio server of 160.56 ms. Meanwhile, for downloading cloud storage files that have the highest average throughput value, nextcloud server is 1,332 kbps. The cloud storage that has the lowest average packet loss value is balanced, because the two cloud storages get the same packet loss value of 0%. The cloud storage that has the lowest average download delay is the nextcloud server at 132,057 ms, while the cloud storage that has the lowest jitter is the nextcloud server at 132,139 ms.